Spiral superconducting nanowire single-photon detector with efficiency over 50% at 1550 nm wavelength. (8th June 2017) - Huang, J; Zhang, W J; You, L X; Liu, X Y; Guo, Q; Wang, Y; Zhang, L; Yang, X Y; Li, H; Wang, Z; Xie, X M
Abstract: Superconducting nanowire single-photon detectors (SNSPDs) are widely used for the detection of visible and near-infrared single photons. Due to the nature of the polarization sensitive absorption of the nanowire, the detection efficiency (DE) of the meander SNSPD is polarization sensitive. In order to obtain a polarization-insensitive device with high DE, we fabricated NbN SNSPDs with spiral structure, which were embedded into an optical cavity. No meaningful current crowding effect was observed in the spiral SNSPDs. The spiral SNSPD showed a maximal system detection efficiency of 52.5% at 1550 nm with a dark count rate of 100 Hz and a polarization extinction ratio of 1.04, due to the combination of a spiral geometry and an optical cavity.